Harmonic reduction under unbalanced operating conditions of PV‐connected cascaded H‐bridge multilevel inverters using fault tolerant adaptive phase‐shifted pulse width modulation. (21st January 2019) - Eroğlu, Fatih; Kurtoğlu, Mehmet; Arslan, Ali Osman; Vural, Ahmet Mete
Summary: Balanced operating conditions of photovoltaic (PV)‐connected cascaded H‐bridge multilevel inverters (CHB‐MLIs) require equal number of series and parallel arrays, equal amplitude modulation indices, and same environmental conditions such as temperature and irradiance for each H‐bridge (cell). Unbalanced operating conditions arise when at least one of these requirements are not met and/or a DC fault occurs. Phase‐shifted pulse width modulation (PS‐PWM) is the most widely used technique for CHB‐MLIs. However, under unbalanced operating conditions, harmonics that appear around the effective switching frequency ( f s w ) of each cell fail to eliminate each other when PS‐PWM is used, and consequently, undesired harmonics are generated at the multiples of f s w on the output voltage of CHB‐MLI. In this paper, a fault tolerant adaptive phase‐shifted pulse width modulation (FTA‐PS‐PWM) method is proposed for any number of cells to overcome this problem. For this reason, a mathematical representation of the harmonics appearing around the multiples of f s w on the output voltage of CHB‐MLI is suggested. In this analysis, on/off instants of the power semiconductors are investigated in frequency domain for a single carrier period. Based on derived formulations, phase angle of each cell is calculated at each sampling time using DC voltages and amplitude modulation indices of all cells in FTA‐PS‐PWM. In order to validate the usefulness of the proposed switching strategy, a three‐phase, PV‐connected CHB‐MLI is established in simulation environment and a prototype of a single‐phase CHB‐MLI is built. It is shown that FTA‐PS‐PWM reduces output voltage harmonics effectively in unbalanced operating conditions including DC faults for different number of cells. Moreover, FTA‐PS‐PWM is also compared with previous methods in the literature and compliance of output harmonics with international standards is examined for various cases. The results reveal that FTA‐PS‐PWM generally provides better results in terms of individual harmonics and total harmonic distortion of output voltages of CHB‐MLI and satisfies the requirements of the standards.